Investigation of flammability of cross laminated timber using pressure infusion of magnesium-based flame retardant - Kwek, Jia Wei (2019)
Wood has been used for thousands of years due to its versatility and aesthetic properties. Innovations have kept wood competitive as a building material compared to materials like concrete for which the carbon footprint is quite high. Cross Laminated Timber (CLT) is one such innovation to improve the mechanical properties of wood. However, the flammability of wood is still a safety concern for the usage. Magnesium potassium phosphate (MKP) is commonly used in construction and repair works, as a quick-setting cement. The study aims to explore the viability of precipitating MKP in CLT, as a fire-retardant treatment. The CLT was pressure infused with Magnesium Acetate (MgAc) and Monopotassium Phosphate (KDP) as reactants for MKP. Thermal analysis using Differential Scanning Calorimetry (DSC) and Thermogravimetric Analysis (TGA) showed increased residue, possibly a result of char promotion. The time taken was improved for the treated CLT layers to fail, compared to the untreated CLT during the direct flame torching test. Despite this, when the samples are exposed to a simulated ISO 834 fire curve in a furnace, the data was not conclusive to determine any effects of fire retardancy by the MKP treatment. A 28-day natural weathering test was conducted using the treated CLT, and the thermal properties of the MKP-treated CLT was observed with the torching test. The results have shown that weathering does reduce the performance of fire protection provided by MKP. This was supported by the changes in DSC curves and TGA wt% loss. Overall, the weathered MKP-treated CLT still possess better fire properties over untreated CLT samples. This study serves to demonstrate the foundation of MKP pressure infusion treatment as a fire-retardant treatment. Further studies must be conducted to cover all aspects required for MKP to be a fire-retardant product.